Simulation model for investigating safety margin of three-layer molten pool after late phase in-vessel water injection. (December 2022) - Li, Zongyang; Chang, Huajian; Chen, Lian; Han, Kun; Fang, Fangfang
Abstract: The thermal focusing effect is an essential issue in the research of In-Vessel Retention (IVR) because it might cause vessel failure. Late phase in-vessel water injection is applied to the three-layer corium pool surface to alleviate the severe accident and strengthen the IVR strategy. Analyzing the heat transfer in this corium pool after in-vessel water injection is an important issue. A model named "Three-layeR configuration mOlten pool after the late phase in-vessel water Injection under ERVC-IVR Strategy (TROIS)" has been developed for analyzing the heat transfer issues. Its calculated results could reasonably analyze a two-layer case of AP600 and a three-layer experiment with both the top and sidewall cooling conditions. Furthermore, it is applied to analyze the hypothetical core degradation case of AP1000. The calculated results demonstrate that the safety margin of the two-layer configuration is larger than that of the three-layer configuration. And vessel failure would not occur in the three-layer configuration with or without in-vessel water injection, according to the comparison results of local heat flux and CHF. Late phase in-vessel water injection can alleviate this thermal focusing effect and enlarge the safety margin.